Numerical simulation of local temperature evolution in bituminous materials under cyclic loading. Issue 10 (25th November 2016) - Riahi, E.; Allou, F.; Ulmet, L.; Absi, J.; Dubois, F.; Petit, C.
Abstract : Asphalt concrete is a heterogeneous material containing a viscoelastic bituminous matrix and elastic aggregates. During fatigue testing in the laboratory, the material stiffness decreases as a result of increase in temperature due to self-heating. The objective of this study was to quantify such self-heating, during fatigue testing, as one of the biases affecting the fatigue life estimation of bituminous materials. A heterogeneous approach, which consists of separating the viscoelastic matrix from the elastic aggregates, has been adopted. According to a complex domain approach, a finite element simulation of a cyclic mechanical loading is proposed by taking into account the dissipated energy, internal thermal evolution, temperature dependence of the matrix stiffness and the heat transfer process. In considering a thermomechanical coupling, the numerical simulation results indicate that dissipated energy in the bituminous matrix is influenced by material heterogeneities. A higher dissipated energy can be observed in thin matrix films, where the strain level exceeds that of thicker films. An estimation of temperature evolution using dissipated energy as a heat source is in a good agreement with experimental results. Local temperature variations are dependent on the local heat source, the thermal properties of each phase and aggregate distribution.